Experiências da residência pedagógica no ensino de língua inglesa em uma escola de tempo integral de Araguaína- TO. - Ataide, Bruna Aguiar (Universidade Federal do Tocantins, 2022)
The present qualitative approach and bibliographic nature research intends to describe the experience of academics (residents) from the English Language and Literatures course of the Federal University of Tocantins, during the Pedagogical Residency Program (PRP) in a fulltime school, which aim presents results and contributions to the academic training of residents. Carried out based in the Institutional Project of Pedagogical Residency at the Federal University of Tocantins, in the notice 06/2018, and in authors such as Poladian (2014), Arroyo (1988) and Pimenta (1996). The data for analysis were generated from the reports of the Pedagogical Residency, in which we identified what were the conclusions and reflections during the experience of residents in the basic education scenario. In the first instance, we present the Program, its characteristics, and its objectives. Then, we highlight aspects of full-time field school, and soon after, we discuss some of the benefits resulting from PRP for the academic training of English language teachers. As a result, we can conclude that, in fact, the Pedagogical Residency is a program of great relevance in the process of improving teacher training and that it contributes significantly to the preparation of future teachers.